Convertible bond valuation focusing on Chinese convertible bond market - Yang, Ke (2010)
This paper mainly discusses the methods of valuation of convertible bonds in Chinese market. Different from common convertible bonds in European market, considering the complicate features of Chinese convertible bond, this paper represents specific pricing approaches for pricing convertible bonds with different provisions along with the increment of complexity of these provisions. More specifically, this paper represents the decomposing method and binomial tree method for pricing both of Non-callable, Non-puttable Convertible Zero-coupon bond, Pricing Callable, Non-puttable Convertible Zero-coupon bond and Pricing Callable, Puttable Convertible Zero-coupon bond. Additionally, this paper gives out one possible solution for pricing Callable, Puttable, Resettable Convertible Zero-coupon bond. Furthermore, influence of company’s credit risk on valuation of convertible bond is discussed as well. According to the analysis of valuation error, some possible improvements in the valuation process are represented.